VITAMINS AND MINERALS ADMINISTRATION IN COMPLEX SANITATION OF YOUNGER SCHOOLCHILDREN - A.V. Pochivalov; N.A. Fokina ("Paediatrician" Publishers LLC, 2010)
One of actual modern problems of prophylactic pediatrics is provision of schoolchildren with vitamins and minerals. The years of school education are the years of rapid growth and pubescence. Adaptation in group, mental and physical loads increase the need of growing organism in main nutritive materials and energy. The article presents the results of a study of effectiveness of vitamins and minerals complex «ALFAVIT Schoolchild» in younger schoolchildren. Key words: vitamins, schoolchildren, prophylaxis.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):126-130)